Design and Occupant-Protection Performance Analysis of a New Tubular Driver Airbag. (April 2018) - Zhou, Huajian; Zhong, Zhihua; Hu, Manjiang
Abstract: An airbag is an effective protective device for vehicle occupant safety, but may cause unexpected injury from the excessive energy of ignition when it is deployed. This paper focuses on the design of a new tubular driver airbag from the perspective of reducing the dosage of gas generant. Three different dummies were selected for computer simulation to investigate the stiffness and protection performance of the new airbag. Next, a multi-objective optimization of the 50th percentile dummy was conducted. The results show that the static volume of the new airbag is only about 1/3 of the volume of an ordinary one, and the injury value of each type of dummy can meet legal requirements while reducing the gas dosage by at least 30%. The combined injury index ( P comb ) decreases by 22% and the gas dosage is reduced by 32% after optimization. This study demonstrates that the new tubular driver airbag has great potential for protection in terms of reducing the gas dosage.